PELATIHAN PENGGUNAAN APLIKASI PENDETEKSI PALGIAT UNTUK DOSEN UNIVERSITAS LANCANG KUNING - Alexsander Yandra; Zamzami; Bayu Febriadi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2018)
University Lancang Kuning which is one of the leading educational institutions in Riau province, also produces superior products that are outstanding students and ready to face the world of sprinting and outstanding lecturers, as stated in the yellowish university mission "Becoming a University of Excellence at National level based Malay culture ". Student research and lecturers refer to many previous studies, sometimes there are students or lecturers copy paste existing research without understanding that later what they copied from the research the person will make them as a plagiarist